Schools of Strategic Thoughts on Russia in the Us Expert Community - I. A. Safranchuk (Vestnik MGIMO-Universiteta, 2015)
This article is devoted to the schools of strategic thought on Russia in the US expert community. The author suggests and underpins the system to classify US schools of strategic thoughts on Russia. Based o this classification the author extracts intellectuals fields, within which schools of strategic thought emerge and exist. The suggested methodology is retrospectively applied to describe the evolution of US schools of strategic thoughts on Russia in the period after the collapse of the Soviet Union and until the present. The article also dwells on the major contemporary US schools of strategic thought on Russia. Their origins are traced and basic characteristics summarized. Four such schools of thought are suggested, namely - skepticism, alarmism, realism and unconditional cooperation. The author not only describes the schools of thought as such, but also analyses the dynamics of their interactions. The schemes, summarizing the major thesis of the article, must facilitate the reading process. The suggested methodology can be applied by other authors for further analysis of US debates on Russia and US-Russian relations.